(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This contribution examines the implementation of the African Union Convention for the Protection and Assistance of Internally Displaced Persons in Africa (Kampala Convention) by relevant actors in Cameroon. It highlights the fact that there is a considerable gap between the legal provisions of the Kampala Convention and their practical application in Cameroon. On this basis, it argues that there is an urgent need to take necessary measures to reduce or close such a gap and thus improve the plight of the more than a million civilians who had been internally displaced as a result of deadly attacks by non-state armed groups in the far North region, growing violence in the English-speaking North-West and South-West regions and natural disasters. The approach envisaged to achieve this demonstration is articulated in three stages. First, the article sheds light on the huge scale of internal displacement in Cameroon and on the precarious situations of those who are victims of it. Then, through a critical approach, it discusses the limitations and difficulties that prevent the Kampala Convention from fully contributing to the improvement of the lot of IDPs in Cameroon. Finally, with an approach centred around making suggestions for law reform, the article puts forward possible solutions aimed at strengthening the implementation of the Kampala Convention in Cameroon.